Мотив одиночества в раннем творчестве Ирен Немировски - Bortnowski, Antoni (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2020)
The subject of analysis in this paper is the motif of loneliness in the early works of Irène Némirovsky (1903–1942). A pessimistic view on human life, which is typical for Némirovsky, is shown by the author of this article on the example of three works: L’Enfant génial, David Golder and Les Mouches d’automne. The main character of each of the works constantly feels misunderstood, alienated and eventually dies, convinced of the meaninglessness of his/her existence. These feelings become common for the characters, which at first glance seem completely different - a Jewish boy from the poor quarter of Odessa, a rich financier living in Paris, and an elderly Russian nanny, who emigrates with her masters. The problem of loneliness in Némirovsky’s writing is closely related to the issues of finding one’s own identity and attempts to overcome the past.